Comparison of Adipocyte Viability After Short-Term Cryopreservation of Adipose Aspirates Through 3 Different Techniques - Kocak, Polen; Unsal, Naz; Canikyan, Serli; Kul, Yaren; Cohen, Steven R.; Tiryaki, Tunc (OXFORD UNIV PRESS, 2023)
Background: Effective cryopreservation allows for the long-term storage of living cells or tissues with the possibility of later clinical applications. Unfortunately, no successful investigations on the long-term preservation of adipose aspirates for prospective autologous fat grafting have been conducted. Objectives: In this study, we aimed to compare 3 different freezing methods to preserve adipose aspirates obtained from conventional lipoplasty to determine the optimal cryopreservation technique. Methods: To determine the optimal cryopreservation technique, hematoxylin and eosin staining, MTS assay, and Annexin assay were performed on each of the 3 groups plus a fourth control group. Group 1 served as the control, and fat tissue was analyzed immediately after adipose harvesting with no cryopreservation. For experimental Group 2, 15mL of adipose aspirates were directly frozen at -80 degrees C for up to 2 weeks. For experimental Group 3, 15mL of adipose aspirates were frozen inside the adi-frosty containing 100% isopropanol and stored at -80 degrees C for up to 2 weeks. For experimental Group 4, 15mL of adipose aspirates were frozen with freezing solution containing 90% fetal bovine serum (v/v) and 10% dimethyl sulfoxide (v/v). Results: The results demonstrated that the experimental Group 3 had significantly more live adipocytes and greater cellular function of adipose aspirates than the experimental Groups 2 and 4. Conclusion: Cryopreservation with adi-frosty containing 100% isopropanol appears to be the best means of cryopreservation of fat.
Keywords: FAT TRANSFER; SURGICAL-MANAGEMENT; DIMETHYL-SULFOXIDE; GYNECOMASTIA; GRAFTS; TISSUE; LIPOSUCTION; LIPECTOMY; CELLS; SKIN; Surgery